The Behavior of Brazilian Senators: Analyzing the Exchange of Votes inside the Fixed Committees during the 52nd Legislature - Mauerberg Junior, Arnaldo; Strachman, Eduardo; Reami, Daniela (Revista de Economia, 2013)
Using the method of Social Networks Analysis, we’ll try to see if politicians swap votes between them seeking support for their projects, to this end, we’ll first map the behavior, activities and contacts of the Senators of the Brazilian Federative Republic within all the fixed committees which had some vote during the 52nd Legislature, then we can see the most popular and central Senators to each committee. After this analysis we wish to answer the following question: did logrolling exist in the Brazilian Senate? Previously the empirical analysis and response to the problems posed, we’ll present the necessary theoretical introduction understood by reviewing the literature on relevant subjects, whether they are purely theoretical with respect to the exchange of support, or analytical about the Brazilian political system.